2019
DOI: 10.18805/ag.r-1858
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitive Responses in Plants

Abstract: structurAl hyp e r s e n s I t I v e r e s p o n s eHR is considered a biochemical reaction rather than a structural defense mechanism but can be described REVIEW ARTICLE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Recent studies in resistance spot welding (RSW) of magnesium alloys have demonstrated that dissimilar RSW of magnesium AZ31 to aluminum Al5754 coated with nanostructured electrodeposited coating prevented intermetallic formation while enhancing joint strength. RSW is the most common welding technique used in the automotive industry because it is inexpensive, easily automated, and capable of producing high-quality welds [8]. The process is based on the contact resistance between the metals to be joined and the electrodes [9].…”
Section: Welding Metallurgy Of Magnesium Alloysmentioning
confidence: 99%
“…Recent studies in resistance spot welding (RSW) of magnesium alloys have demonstrated that dissimilar RSW of magnesium AZ31 to aluminum Al5754 coated with nanostructured electrodeposited coating prevented intermetallic formation while enhancing joint strength. RSW is the most common welding technique used in the automotive industry because it is inexpensive, easily automated, and capable of producing high-quality welds [8]. The process is based on the contact resistance between the metals to be joined and the electrodes [9].…”
Section: Welding Metallurgy Of Magnesium Alloysmentioning
confidence: 99%
“…During ETI, a virulencepromoting pathogen effector or its activity inside plant cells is sensed by a plant resistance (R) protein, most of which are NLR (nucleotide-binding domain and leucine-rich repeat) proteins (Jones et al, 2016). This recognition triggers a signaling cascade that usually culminates in a hypersensitive response (HR), a type of programmed cell death thought to contain the pathogen at the site of infection (Mukhtar et al, 2016 andThakur et al, 2019). In many pathosystems, high temperatures compromise ETI.…”
Section: Environmental Impact On Effector-triggered Immunity (Eti)mentioning
confidence: 99%
“…This recognition triggers a rapid and robust defense response, the so‐called effector‐triggered immunity (ETI) (Jones & Dangl, 2006). ETI is often accompanied by a hypersensitive response (HR) at the infection site, a form of programmed cell death (Thakur et al., 2019). However, some PAMPs (e.g., the bacterial Harpin HrpZ protein) can also induce HR in plants (Chang & Nick, 2012).…”
Section: Introductionmentioning
confidence: 99%